NT‐proBNP and All‐Cause and Cardiovascular Mortality in US Adults: A Prospective Cohort Study - Justin B. Echouffo‐Tcheugui; Sui Zhang; Natalie Daya; John W. McEvoy; Olive Tang; Stephen P. Juraschek; Chiadi E. Ndumele; Josef Coresh; Robert H. Christenson; Elizabeth Selvin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) is strongly associated with mortality in patients with heart failure. Prior studies, primarily in middle‐aged and older populations, have suggested that NT‐proBNP has prognostic value in ambulatory adults. Methods and Results We conducted a prospective cohort analysis of adults, aged ≥20 years, in the nationally representative 1999 to 2004 National Health and Nutrition Examination Survey, to characterize the association of NT‐proBNP with mortality in the general US adult population overall and by age, race and ethnicity, and body mass index. We used Cox regression to characterize associations of NT‐proBNP with all‐cause and cardiovascular disease (CVD) mortality through 2019, adjusting for demographics and cardiovascular risk factors. We included 10 645 individuals (mean age, 45.7 years; 50.8% women; 72.8% White adults; 8.5% with a self‐reported history of CVD). There were 3155 deaths (1009 CVD‐related) over a median 17.3 years of follow‐up. Among individuals without prior CVD, elevated NT‐proBNP (≥75th percentile [81.5 pg/mL] versus <25th percentile [20.5 pg/mL]) was associated with a significantly higher risk of all‐cause (hazard ratio [HR], 1.67 [95% CI, 1.39–2.00]) and CVD mortality (HR, 2.87 [95% CI, 1.61–5.11]). Associations of NT‐proBNP with all‐cause and CVD mortality were generally similar across subgroups defined by age, sex, race and ethnicity, or body mass index (all P interaction >0.05). Conclusions In a representative sample of the US adult population, NT‐proBNP was an important independent risk factor for all‐cause and CVD mortality. NT‐proBNP may be useful for monitoring risk in the general adult population.